Clusters of bioactive compounds target dynamic endomembrane networks in vivo - Drakakaki, Georgia (National Academy of Sciences, 2011)
Endomembrane trafficking relies on the coordination of a highly complex, dynamic network of intracellular vesicles. Understanding the network will require a dissection of cargo and vesicle dynamics at the cellular level in vivo. This is also a key to establishing a link between vesicular networks and their functional roles in development. We used a high-content intracellular screen to discover small molecules targeting endomembrane trafficking in vivo in a complex eukaryote, Arabidopsis thaliana. Tens of thousands of molecules were prescreened and a selected subset was interrogated against a panel of plasma membrane (PM) and other endomembrane compartment markers to identify molecules that altered vesicle trafficking. The extensive image dataset was transformed by a flexible algorithm into a marker-by-phenotype-by-treatment time matrix and revealed groups of molecules that induced similar subcellular fingerprints (clusters). This matrix provides a platform for a systems view of trafficking. Molecules from distinct clusters presented avenues and enabled an entry point to dissect recycling at the PM, vacuolar sorting, and cell-plate maturation. Bioactivity in human cells indicated the value of the approach to identifying small molecules that are active in diverse organisms for biology and drug discovery.